Learning to mentor in sports coaching a design thinking approach - Chambers, Fiona C. (Routledge research in sports coaching, 2018)
Learning to Mentor in Sports Coaching is an innovative, user-friendly practical and theoretical guide for educating sports coaches as mentors. It is the first book to employ design thinking techniques to develop a new approach to mentor education in sports coaching. Providing theoretical grounding in mentoring conversations, design thinking, and case study research, the book centres on a series of redesigned mentoring conversations between some of the world's leading sports coaching experts, coach educators, mentors and mentees.